Experimental Study About Effect Iron Slag on The Shear Strength of Reinforced Concrete Beams Without Shear Reinforcement - M. Hussein, Mariam Ibraheem; M. Rasheed , Mohammed (International Journal of Sustainable Construction Engineering and Technology, 2023)
In the last decades, researchers have become more interested in the environmental aspect of investing materials harmful to the environment in various aspects of life, including construction. Slag is considered as one of the industrial wastes that are harmful to the environment. There are many studies on the use of slag as a substitute for building materials because it adds an excellent property to concrete. In this study, the iron slag was used as a partial replacement of coarse aggregate and fine aggregate in different proportions, the study conducts to know its effects on the shear strength of reinforced concrete beams. Ten R.C. beams without shear reinforcement (1100×100×200) mm were studied using iron slag as a coarse aggregate with a ratio of 10%, 20%, 30% and 40%, as a fine aggregate with a ratio of 10%, 20% and 30%, and partial substitute for coarse aggregate by 7.5% and partial substitute for fine aggregate by 7.5% in the same model, finally, partial substitute for coarse aggregate by 15% and partial substitute for fine aggregate by 15% in the same model. According to the test results, it was found that the optimal proportion of replacing slag with coarse aggregate is 20%, which resulted in a 24.58% increase in peak load. While the optimal proportion of replacing slag with fine aggregate by 20%, resulting in a 24.3% increase in peak load.